The Perils of Marketing Weight-Management Remedies and the Role of Health Literacy. (April 2015) - Bolton, Lisa E.; Bhattacharjee, Amit; Reed, Americus
This research explores the impact of weight-management remedy marketing on healthy lifestyle behaviors. Three studies demonstrate that exposure to drug (but not supplement) marketing for weight management encourages unhealthy consumer behavior as a result of consumers' reliance on erroneous beliefs about health remedies. The authors explore the possible mitigating role of two dimensions of healthy literacy: nutrition knowledge and remedy knowledge. Whether measured or manipulated, the results show remedy knowledge to be more effective than nutrition knowledge at lessening the effect of weight-management drug marketing on unhealthy behavior. The authors close with a discussion of the theoretical and substantive implications of this research for consumer welfare.